WFS1 Gene–associated Diabetes Phenotypes and Identification of a Founder Mutation in Southern India - Chapla, Aaron; Johnson, Jabasteen; Korula, Sophy; Mohan, Nisha; Ahmed, Anish; Varghese, Deny; Rangasamy, Parthiban; Ravichandran, Lavanya; Jebasingh, Felix; Kumar Agrawal, Krishna; Somasundaram, Noel; Hesarghatta Shyamasunder, Asha; et al. (The journal of clinical endocrinology and metabolism, 2022)
Abstract Context Wolfram syndrome (WFS) is a rare autosomal recessive disorder characterized by juvenile-onset diabetes, diabetes insipidus, optic atrophy, deafness, and progressive neurodegeneration. However, due to the progressive nature of the disease and a lack of complete clinical manifestations, a confirmed diagnosis of WFS at the time of onset of diabetes is a challenge. Objective With WFS1 rare heterozygous variants reported in diabetes, there is a need for comprehensive genetic screening strategies for the early diagnosis of WFS and delineating the phenotypic spectrum associated with the WFS1 gene variants in young-onset diabetes. Methods This case series of 11 patients who were positive for WFS1 variants were identified with next-generation sequencing (NGS)–based screening of 17 genemonogenic diabetes panel. These results were further confirmed with Sanger sequencing. Results 9 out of 11 patients were homozygous for pathogenic/likely pathogenic variants in the WFS1 gene. Interestingly, 3 of these probands were positive for the novel WFS1 (NM_006005.3): c.1107_1108insA (p.Ala370Serfs*173) variant, and haplotype analysis suggested a founder effect in 3 families from Southern India. Additionally, we identified 2 patients with young-onset diabetes who were heterozygous for a likely pathogenic variant or a variant of uncertain significance in the WFS1 gene. Conclusion These results project the need for NGS-based parallel multigene testing as a tool for early diagnosis of WFS and identify heterozygous WFS1 variants implicated in young-onset diabetes.